The Difference of Plaque Acidity between Chewing Sucrose Dark Chocolate and Xylitol Dark Chocolate in Children aged 10-12 Years - Yudiatna, Clara Cessa Putri; Kaswindiarti, Septriyani; Suparno, Nilasary Rochmanita; Karyadi, Edi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This study aims to determine the difference of plaque acidity between chewing sucrose dark chocolate and xylitol dark chocolate in children aged 10-12 years. Methodology: Quantitative research using by a quasi-experimental with a non-equivalent control group design. Twenty-one children had their plaque acidity measured before and after chewing sucrose dark chocolate and xylitol dark chocolate. Measurement of the plaque acidity before chewing sucrose and xylitol dark chocolate was carried out by taking plaque samples using an excavator on the buccal, palatal, or lingual, and proximal surfaces of the first permanent molars, then dissolving them in a test beaker containing 2.5 ml of deionized water. Measurement of the degree of plaque pH is carried out using a pH meter which is measured three times and the final result is obtained from the average. The same procedure was carried out to measure the degree of plaque acidity after 20 minutes of chewing sucrose and xylitol dark chocolate. The measurement results were analyzed using the independent t-test. Results: Data analysis was carried out using an independent t-test and tabulated using SPSS 22. There was a significant difference in plaque acidity between subjects who chewed sucrose dark chocolate (x̄ = 6.2794 ± 0.11425) and xylitol dark chocolate (x̄ = 6.4079 ± 0.10269). Applications/Originality/Value: The difference between this study and previous research is this study measured differences in the degree of plaque acidity in subjects who chewed sucrose dark chocolate and xylitol dark chocolate the measurement time was used as a variable.